Hubungan Kompetensi Pedagogik Instruktur dengan Motivasi Berprestasi Peserta Pelatihan Administrasi Perkantoran di UPT Balai Latihan Kerja Jember - Rya Agustin (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The pedagogical competence of instructors refers to the instructors’ proficiency in the teaching and learning process in training programs. Competent instructors will enhance the motivation of training participants. The lack of instructor competence in managing learning will affect the participants’ proficiency in training. If training participants have low proficiency, they will have difficulty in carrying out work activities. The worst impact is that training participants are unable to compate with other workers. If this happens, the goal of training to create highly competitive graduates has not been fully achieved. Therefore, it is important to motivate training participants to achieve success. The type of research used in this study is correlational research with a quantitative approach. The technique for determining the research location uses purposive area technique, with respondent determination using total sampling, namely 32 participants of the institutional training program in office administration sub major in 2023. The data collection technique used questionnaires and documentation. The questionnaires in this study were analyzed using Pearson product moment correlation through SPSS (Statistical Package for the Social Sciences) version 26. Based on the data analysis results, it was found that there is a correlation between the pedagogical competence of instructors and the achievement motivation of office administration training participants at the Jember Training Center Work Unit. The correlation results fall into the category of somewhat low interpretation. This is because achievement motivation can be influenced by other factors not observed in this study.
Repo 16 Juli 2026_ Rudy K Finalisasi 16 Juli 2026_Yudi
Keywords: pedagogical competence; achievement motivation; training